Analisis Gas Darah pada Kucing yang Mengalami Laparohisterotomi dengan Anestesi Xylazin-Ketamin dan Xylazin-Propofol (BLOOD GAS ANALYSIS OF XYLAZIN- KETAMIN AND XYLAZIN-PROPOFOL FOR ANESTHESIA TO LAPARO-HISTEROTOMY SURGERY IN CAT) - Yudaniayanti, Ira Sari; Triakoso, Nusdianto; Galijono, Djoko (Jurnal Veteriner; Vol 12 No 1 (2011), 2012)
The aim of this research was to study the safety application of xylazine-ketamine and xylazinepropofolrecurrent dosage combination as anesthesia for laparo-histerotomy surgery in cat. Thisresearch used 10 female cats, 12-18 months of age, followed randomly divided into two groups, P1:atropine 0,04 mg/kgBW/SC + xylazine 2 mg/kg BW/IM + ketamine 20 mg/kg BW/IM; P2 : atropine0,04mg/kg BW/SC + xylazine 2 mg/kg BW/IM + Propofol 20 mg/kg BW/IV. The blood of the allgroups was taken from vena femuralis at 0 minute (before treatment), 15, 30, 45 and 60 minutesduring anesthesia for measurement of blood gas value pH, pCO2 and HCO3. After all animals wereanesthetized, the animals were treated laparo-histerotomy surgery. The data were analyzed byusing Randomized Complete Block Design (RCBD). The result showed both of groups were notsignificantly difference (p>0,05) to blood gas values for pH, pCO2 dan HCO3. Besides, both groupsanaesthetic agent perfectly caused metabolic acidosis with respiratory alkalosis compensationperfectly, therefore it is relatively safe to use as anaesthetic agent for surgery that needs long timeprocedure, as laparo-histerotomy.
Keywords: Xylazine, ketamine, propofol, metabolic acidosis, respiratory alkalosis